PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KONSEP “SUMBER ENERGI DI SEKITAR KITA” KELAS III SD NEGERI ASEMBAKOR I - Vega Fakis Alhamni; Ribut Prastiwi Sriwijayanti; Ani Anjarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The reality in the field shows that science teachers still use the Teacher Centered Learning (TCL) model. Teachers still dominate the learning process so that some students still look passive and are less brave in expressing ideas. The purpose of this study is to improve student learning outcomes on the concept of energy sources around us in class III of Asembakor I Elementary School using the PBL (Problem Based Learning) learning model. This study uses the Classroom Action Research (CAR) method, there are 4 stages of activities in one round (cycle), namely planning, implementation stage, observation stage, and reflection stage. This study has 2 cycles. The third grade students of Asembakor I Elementary School who were the subjects of this study numbered 7 people. The results of this study showed a significant increase in student learning outcomes. Based on the pre-test results, the number of students who did not complete was 6 students (85.71%) and those who completed were 1 student (14.28%). In cycle I there was an increase, namely there were 2 students who completed (28.57%) while those who had not completed were 5 students (71.42%). Then, in cycle II there was an increase, namely there were 6 students who completed (85.71%) while those who had not completed were 1 student (14.28%). Based on these results, it shows that the PBL (Problem Based Learning) learning model can improve student learning outcomes.